Studi Islam; Metode dan Pendekatan Penelitian Tokoh Dalam Lintas Sejarah - Marlian Arif Nasution (UIN Sumatera Utara, 2022)
Methodology of Islamic Studies is oriented towards research methods and approaches. Monoistic understanding of Islam can lead to various conflicts. Therefore, this paper attempts to describe in general the various methods and approaches to produce a comprehensive understanding of Islam. This study uses a non-participant qualitative method by adopting a library research approach. The results obtained are the methods and approaches used by the characters in researching Islamic studies, in terms of the results achieved (exploratory, explanatory), in terms of the use of sources (library research, field research), in terms of how to analyze (qualitative, quantitative), from in terms of basic methods (historical, case, correlational, causal-comparative, experiment, survey, and action research).